Effect of stress management based self-care counseling on glycemic control in women with gestational diabetes mellitus: a randomized controlled trial study - Atefeh Bagheri-Tirtashi; Fatemeh Nasiri-Amiri; Hajar Adib-Rad; Hossein-Ali Nikbakht; Mahbobeh Faramarzi; Ezzat Kiani (BMC Pregnancy and Childbirth)
Abstract Background Stress plays an important role in the consequences of gestational diabetes mellitus [GDM]. It is possible to make a change in the lifestyle by providing counseling in the field of self-care based on stress management in order to avoid the adverse consequences of GDM. Therefore, the present study was designed and implemented with the aim of determining the effect of self-care counseling based on stress management on blood sugar control in women with GDM. Methods A randomized trial with two parallel arms was conducted involving 75 pregnant women diagnosed with GDM at 20–30 weeks of gestation, who were referred to Shohada Hospital in Behshahr city from July 2022 to March 2023. The women with GDM were divided into two groups for intervention and control through random block allocation. The intervention group received 8 virtual counseling sessions once a week for 45–50 min continuously based on stress management, while the control group only received antenatal usual care (AUC). The data were measured before and after the intervention using Fasting Blood Sugar [FBS] and HbA1c (glycated hemoglobin) tests, SDSCA [summary of diabetes self-care activities, NuPDQ‑17 [Prenatal Distress Questionnaire]and DASS [stress, depression and anxiety] questionnaires. Results The mean FBS in the intervention group were significantly lower than the control group after the intervention (P < 0.001, η2 = 0.49). The HbA1c level was lower in the intervention group than in the control group, but not statistically significant (P = 0.078). The mean score of SDSCA after counseling in the intervention group was significantly higher than the control group (P < 0.001, η2 = 0.79). Also, the NuPDQ-17 after counseling in the intervention group was significantly lower than the control group (P < 0.001, η2 = 0.67). Moreover, the mean scores of the depression (P < 0.001, η2 = 0.82), anxiety (P < 0.001, η2 = 0.67) and stress (P < 0.001, η2 = 0.77) were significantly lower in the intervention group than in the control group. Conclusion Stress management-based self-care counseling to prenatal usual care could be considered as an adjunctive care option for reducing on blood sugar and increasing the self-care activities of pregnant women with gestational diabetes and reducing their stress during pregnancy.